Metabolic Disorder of Extracellular Matrix Mediated by Decorin Upregulation Is Associated With Brain Arteriovenous Malformation Diffuseness - Li, Maogui; Liu, Qingyuan; Yang, Junhua; Jiang, Pengjun; Yang, Yi; Zhang, Yanan; Cao, Yong; Wu, Jun; Wang, Shuo (Frontiers in Aging Neuroscience, 2020)
Background and Objective: Diffuse brain arteriovenous malformations (BAVMs) are mixed up with normal brain parenchyma and therefore increase the difficulty of surgical resection, leading to poor surgical prognosis. Since the mechanism underlying BAVM diffuseness remains unknown, a quantitative proteomic analysis was performed to investigate the altered expression of proteins in diffuse BAVMs compared to compact ones. Methods: We performed proteomic analysis on 5 diffuse BAVMs and 5 compact BAVMs. Bioinformatics analysis was conducted to identify potential signals related to BAVM diffuseness. Candidate proteins were then investigated in BAVM specimens using immunofluorescence and Western blot analysis. Tube formation assays were used to investigate the effects of candidate proteins on the angiogenesis of human umbilical endothelial cells (HUVECs). Finally, Masson, Sirius red staining and immunofluorescence were used to evaluate the characteristics of extracellular matrix in BAVM tissues. Result: A total of 58 proteins were found to be differentially expressed between diffuse and compact BAVMs via proteomic analysis. TGF-β (transforming growth factor-beta) signaling pathway, ECM-receptor pathway, relaxin signaling pathway and several other pathways were associated with BAVM diffuseness. TGF-β signaling pathway is associated with the angiogenesis; the role of this pathway in the formation of diffuse BAVMs was investigated, and the decorin (DCN) upregulation played an important role in this process. Immunofluorescence showed that DCN significantly upregulated within and around the malformed vessels of diffuse BAVMs. Functional assays showed that exogenous DCN could promote the tube formation ability of HUVECs through inhibiting the TGF-β signaling pathway and overproducing extracellular matrix. Histological staining demonstrated the overproduction of extracellular matrix in diffuse BAVMs. Conclusion: TGF-β signaling pathway inhibited by DCN in vascular endothelial cells is related to BAVM diffuseness. The metabolic disorder of extracellular matrix caused by DCN upregulation may significantly contribute to the formation of diffuse BAVMs.